2021
DOI: 10.21744/lingcure.v5ns2.1805
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 perceptions, subjective norms, and perceived benefits to attitude and behavior of continuous using of medical mask

Abstract: The purpose of this study was to examine and explain the effect of COVID-19 Perception, subjective norms, and Perceived Benefits on attitudes and Behavior continuous use of medical mask. The population of this study is people in Indonesia who have used medical masks for at least a year. The size of the sample used is 146 people with purposive sampling method. The analytical technique used is Path Analysis using SEM-PLS. The results showed that the COVID-19 perception, subjective norm, and perceived benefits ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…When individuals are in groups, there are certain rules, norms, or beliefs about their proper behavior. The group (family, friends, or co-workers) exerts pressure on individuals who feel they may have a certain behavior regarding the reference group (Yasa et al 2021 ). In other words, SN is “the individual’s beliefs about whether significant others think he or she should engage in the behavior and are assumed to capture the extent of perceived social pressures exerted on individuals to engage in a certain behavior” (Shneor and Munim 2019 ).…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
“…When individuals are in groups, there are certain rules, norms, or beliefs about their proper behavior. The group (family, friends, or co-workers) exerts pressure on individuals who feel they may have a certain behavior regarding the reference group (Yasa et al 2021 ). In other words, SN is “the individual’s beliefs about whether significant others think he or she should engage in the behavior and are assumed to capture the extent of perceived social pressures exerted on individuals to engage in a certain behavior” (Shneor and Munim 2019 ).…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
“…Positive affect is “a state of pleasurable engagement with the environment that elicits feelings, such as happiness, joy, excitement, enthusiasm, and contentment” [ 20 ]. We assessed positive affect using a 7-point Likert scale that ranged from “1 = strongly disagree” to “7 = strongly agree.” Respondents were prompted: “When I think about COVID-19 booster doses, I get… hopeful,” “…happy,” “…enthusiastic,” “…relieved,” and “…confident.” The five items were averaged to create a composite, with higher scores representing more positive responses toward the booster shots ( M = 5.51, SD = 0.94, Cronbach’s α = 0.87).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, SN involves a significant social influence on individuals. When individuals are in a group, they feel that they must have appropriate behavior, usually conditioned by family, friends or peers (Yasa et al, 2021). In this way, SN presents a significant relationship with the individual's attitude (Kotler & Keller, 2015).…”
Section: Research Modelmentioning
confidence: 99%
“…Piroth et al (2020) found empirical evidence for the positive effect of SN on PA in a study on online grocery shoppers. Similarly, Yasa et al (2021) tested how SN had a positive impact on PA wearing a face mask. These arguments allow the following hypothesis: H4: SN is positively related to PA toward entrepreneurship.…”
Section: Research Modelmentioning
confidence: 99%